2007
DOI: 10.1111/j.1440-1789.2007.00782.x
|View full text |Cite
|
Sign up to set email alerts
|

Miliary brain metastasis presenting with dementia: Progression pattern of cancer metastases in the cerebral cortex

Abstract: We report an autopsy case of an 82-year-old woman with progressive dementia due to miliary brain metastasis from lung adenocarcinoma. The patient presented with dementia 5 months prior to death and suddenly died of pulmonary hemorrhage. Postmortem examination revealed normal appearance of the brain. However, there were numerous foci of cancer metastasis in all parts of the brain on light microscopic examination. The carcinoma cells were located in the perivascular (Virchow-Robin) space and did not invade to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 18 publications
6
33
0
Order By: Relevance
“…Miliary brain metastasis is diagnosed on the basis of findings showing diffuse miliary spread of punctate tumor nodules in the brain. Tumor cells are distributed in perivascular spaces without surrounding edema or mass effects [1,6-12], and it is suggested that tumor cells extend through the perivascular spaces into subpial surface [9]. There are no precise diagnostic criteria for miliary brain metastasis, however, and the size of metastatic lesions in cases previously reported ranges widely.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Miliary brain metastasis is diagnosed on the basis of findings showing diffuse miliary spread of punctate tumor nodules in the brain. Tumor cells are distributed in perivascular spaces without surrounding edema or mass effects [1,6-12], and it is suggested that tumor cells extend through the perivascular spaces into subpial surface [9]. There are no precise diagnostic criteria for miliary brain metastasis, however, and the size of metastatic lesions in cases previously reported ranges widely.…”
Section: Discussionmentioning
confidence: 99%
“…However, 4 of 17 cases in which brain MRI was performed did not show any abnormalities [6,7,9,13], and four of 13 cases in which gadolinium-enhanced brain MRI was performed did not show any contrast effects [4,6,11,13]. It is speculated that contrast-enhanced MRI could fail to delineate the metastatic lesions because the blood–brain barrier remains intact at an early point in the clinical course [9,11]. Nemzek et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter pattern is most frequently seen in lymphoma, and breast and gastric carcinoma. Rarely, solid organ tumors have also been reported to metastasize to the perivascular spaces (Virchow‐Robin spaces) without invading underlying parenchyma and is referred to as a miliary pattern of metastasis . The latter is detectable by MRI with gadopentetic acid (Gd‐DTPA) .…”
Section: Discussionmentioning
confidence: 99%
“…[1336] Presence of multiple metastatic tumor foci surrounding blood vessels without parenchymal invasion is described as one pattern of miliary brain metastasis, and has been reported most often with nonsmall cell lung carcinomas. [37] In contrast, meningeal carcinomatosis [Figure 2], which represents subarachnoid dissemination with widespread meningeal studding, is mostly seen in lung and breast carcinomas. [58]…”
Section: Number Of Metastasesmentioning
confidence: 99%